Uganda : Technical Assistance Report-Report on the Prices Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding finalizing the structure and weighting pattern of the export-import price indices (XMPI) and hotels and restaurants producer price index (H and R-PPI). In relation to the XMPI, the structure and weighting pattern for the import price index developed during the previous mission were reviewed and confirmed. Accordingly, plans were developed for an import price survey, including form design and the selection of a sample of importers. Work programs have been drafted and agreed on for (1) the development of the XMPI, (2) the completion of the PPI-manufacturing rebase, and (3) the completion of the H and R-PPI rebase.